(untitled) (Journal of Open Law, Technology & Society, 2016)
This article summarises a doctoral dissertation at the Faculty of Law at the University of Hamburg, Germany. The thesis has been published 2015 as part of a publication series of the Hans-Bredow-Institut, Hamburg, with NOMOS Publishing House, Baden-Baden. The dissertation herein summarised provides a concrete legal substantiation of an accountability of the State to enact a regulatory framework which ensures vendor independent data formats in the private market (below chapter VI-VII). As a result, this work offers the necessary objective, perspective, regulatory means and the avoidance of complex evidential problems to legally ensure interoperability in the market of telematics.In order to derive these results the economic, social and technical background as well as the actual existing influence possibilities of the State must be outlined first (chapter I-V). Although the findings summarised here are primarily derived from German law they are likely to be applicable to other European legislations as well due to the fact that German law is considerably superimposed by European telecommunication law.